Social media in the courtroom: a new era for criminal justice? - Hoffmeister, Thaddeus (Praeger, 2014)
"Social media hasn't just changed society--it's changing the way in which criminal law is prosecuted, defended, and adjudicated. This fascinating book explains how"--